Prospective Study of Isolated Recurrent Tumor Re-irradiation With Carbon-Ion Beams - Shirai, Katsuyuki; Ohno, Tatsuya; Saitoh, Jun-ichi; Okamoto, Masahiko; Katoh, Hiroyuki; Murata, Kazutoshi; Kawamura, Hidemasa; Musha, Atsushi; Abe, Takanori; Mizukami, Tatsuji; Akahane, Keiko; Nakano, Takashi (Frontiers in Oncology, 2019)
Purpose: To perform a prospective study to evaluate the efficacy and safety of isolated recurrent tumor re-irradiation with carbon-ion radiotherapy (RT). Methods and Materials: The inclusion criteria were clinically proven recurrent tumors, measurable by computed tomography or magnetic resonance imaging, patients ≥ 16 years old, performance status scores between 0–2, isolated tumor at a previously irradiated site, and a life expectancy > 6 months. The exclusion criteria were tumor invasion into the gastrointestinal tract or a major blood vessel, uncontrolled infection, early recurrence (< 3 months), and severe concomitant diseases. The primary end-point was the local control rate, the secondary end-points including the overall survival rate, and adverse events. Results: Between December 2013 and March 2016, 22 patients were enrolled in this prospective study. All patients were re-irradiated with carbon-ion RT with radical intent. Five patients had rectal cancer, 4 had sarcoma, 4 had lung cancer, 3 had hepatic cell carcinoma, and 6 had other tumors. The median follow-up time was 26 months. Eight patients developed local recurrence, and the 1- and 2-year local control rates were 71% and 60%, respectively. Eight patients died of their cancers and 2 died of other diseases. The 1- and 2-year overall survival rates were 76% and 67%, respectively. There were no grade 2 or higher acute adverse events and 4 patients (18%) developed grade 3 late adverse events. The group with the longer interval (> 16 months) between the first RT and re-irradiation had significantly better outcomes than the shorter interval group (≤ 16 months). Conclusions: Re-irradiation, using carbon-ion RT with radical intent, had favorable local control and overall survival rates without severe toxicities for selected patients. Re-irradiation has the potential to improve clinical outcomes for isolated, local, recurrent tumors; further investigations are required to confirm the therapeutic efficacy.